Pengaruh Teknik Audio-Tactile Synchronization (ATS) Terhadap Nyeri dan Komplikasi pada Pasien Pasca Operasi Laparotomi di RSU Setio Husodo Kisara - LATIFAH, LATIFAH; Suhita, Byba Melda; Puspitasari, Yenny (Jurnal Ragam Pengabdian, 2026)
Postoperative pain following laparotomy remains a major challenge as it may delay recovery and increase the risk of complications. This study examined the effect of Audio-Tactile Synchronization (ATS) on pain intensity and complications among laparotomy patients. A quasi-experimental pretest-posttest control group design was conducted with 114 participants (57 ATS, 57 control) selected through purposive sampling. Pain was assessed using the Numeric Rating Scale, while complications were evaluated using physiological indicators. Data were analyzed using Friedman, Wilcoxon, and Mann-Whitney tests (α = 0.05). Before intervention, moderate pain was reported by 89.5% of the intervention group and 86.0% of the control group. By day three, mild pain was achieved by 64.9% of the ATS group compared to 49.1% of the control group. Significant pain reductions occurred in both groups (p < 0.001). Complication scores also declined significantly (p < 0.001), with median scores decreasing from 4 to 1 in the ATS group by day two, while remaining 3 in the control group. Between-group differences were significant on day two (p = 0.016) and day three (p < 0.001). ATS effectively reduced postoperative pain and accelerated recovery from complications, supporting its integration as an evidence-based complementary nursing intervention for laparotomy patients